(3QSGdI aj CSeGA GdQShe GdeQSheI Ydi GdBdI GdeSeGg HGdCSWQdGH GdTeGdis
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI eNJUQI GPcQ ajgG CSeGA GdQShe GdeQSheI YdiGdBdI GdeSeGg HGdGSWQdGH GdTeGdi PGJ UaGFM hHYV CYeGdgG s
(3BNQgG (B:s
(3ajfHZi Cf JYed Ydi GdQHY GdCTYI hGdeOGQGJ MJi efg (B( (3cPG (B) (3eG PcQfGg hjchf eKd gPg GdUhQg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B40 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B123) s
Keywords: (3Gdadcs